(untitled) (Global Journal of Human-Social Science, 2025)
Due to the pandemic, people began to have different needs and interests than they were used to and felt a need for guidance on what to think and what to do both individually and collectively. They began to question pre-established concepts in various social sectors, seeking satisfactory answers that would lead them to a stable and significant quality of life in both the short and long term. Is it possible to promote this type of guidance today? What can work to achieve this goal? This article shows that Jehovah’s Witnesses use a literacy approach -Critical Literacy (CL) in their teaching of the Bible with the aim of leading students to constant reassessment and building themselves anew, paving a path for action, transformation and protagonism. This process of protagonism involves forming a critical consciousness in the student and moving them towards positive changes in both the short and long term. Inserted with this approach, Jehovah’s Witnesses have used rhetorical questions and opinions in one of their study publications, called Enjoy Life Forever!. In this material, in addition the questions, there are videos and illustrations that help students empathize with other contexts and similar situations, giving them the opportunity to learn answers and solutions to their questions and problems. However, the use of the Critical Literacy approach does not, in itself, guarantee the achievement of educational objectives.